THE DISCLOSURE OF FINANCIAL INSTRUMENTS IN THE FINANCIAL STATEMENTS IN FINANCIALISATION ERA (Research Bulletins of the Faculty of Economic Sciences, 2018)
The subject of this article is the phenomenon of financialisation and its impact on the information content in financial statements of financial entities with non-financial business profile. The article explains the concept of financialisation, presents the role of accounting in the era of financialisation and shows the impact of financialisation on the information content of financial statements of listed companies outside the financial sector.
Keywords: financialisation, financial instruments, financial statements, listed companies, financial assets